Layoverland : a novel - Noone, Gabby (Razorbill, 2020)
When seventeen-year-old Beatrice arrives in Purgatory and is chosen to help others reach Heaven, the last thing she expects is to fall in love with Caleb, with whom she shares a tragic history.--